Temporal structures in perception and attention - Echeverria Altuna, I (2024)
The world changes over time, but often in structured ways. In turn, temporal structures modulate cognitive processes ranging from perception to attention. This thesis investigates of how perception and attention are tuned to two kinds of temporal structures in the environment: feature regularities and temporal regularities. In Chapter 2, feature regularities across different timescales are found to jointly modulate perception. Chapter 3 reveals that external attention is flexibly oriented to temporally regular visual and auditory features in the absence of spatial and motor certainty. Finally, Chapter 4 unmasks that the prioritisation of sensory (visual and auditory) and action-related contents co-existing in working memory is flexible, temporally tuned, and yet functionally decoupled. Together, these findings unveil the ins and outs of how perception and attention are jointly guided by unique combinations of sensory contents and guidance signals such as expectations and task goals. Furthermore, the present thesis highlights the epistemological and methodological challenges posed by the temporal dimension and by cross-modality translation to the study of cognitive processes such as perception and attention. In summary, this thesis furthers our understanding of how regularities in sensory events unfolding in time, together with dynamic changes in the dispositions of our mental life, jointly modulate perception and attention.